Novel causes of human hypoketotic, hypoinsulinaemic hypoglycaemia. (25th February 2016) - Leiter, Sarah; Kummer, Sebastian; Harris, Julie; Welters, Alena; Williams, Rachel; Hussain, Khalid; Korsch, Erckhart; Meissner, Thomas; Semple, Robert
Abstract: Background: Congenital hyperinsulinaemic hypoglycaemia is characterised by low serum concentrations of ketones, fatty acids, and branched chain aminoacids, and by a requirement for glucose infusion of more than 10 mg/kg per min to maintain euglycaemia. The disorder is caused by physiologically inappropriate insulin secretion. We have recently described a form of hypoglycaemia with a similar metabolic profile, but with undetectable insulin, relatively low glucose requirement, and left-sided hemihypertrophy caused by an activating mutation in AKT2 . Methods: Four children (aged 4 months to 11 years) with hypoglycaemia in the absence of elevated serum insulin and ketones and wild-type AKT2 sequence underwent whole-exome sequencing with their parents. Variants were verified with Sanger sequencing and restriction fragment length polymorphism assays. Serum starved primary dermal fibroblasts were used for immunoblotting against phosphorylated AKT to look for basal hyperactivation of the PI3K–AKT pathway. Findings: Tissue and lymphocyte DNA from one patient with hypoglycaemia, macrocephaly, and fibrous liver disease revealed a mosaic mutation (p.Glu726Lys) in PIK3CA, encoding the p110α catalytic subunit of phosphoinositide-3-kinase. Dermal fibroblasts showed a small but significant (pAKT Thr308 p<0·01, Thr473 p<0·05; one-way ANOVA) increase in basal AKT phosphorylation compared with control cells, in contrast to the large hyperactivation caused by somatic hot-spot PIK3CA mutations in other forms of overgrowth. Another child, who presented with infantile hypoglycaemia and jejunal atresia, had mutations in two constituents of mTORC2 ( mTOR and MLST8 ), which lies upstream from AKT2 in the insulin signalling pathway. Since one variant was inherited from each unaffected parent, these constituents are being evaluated functionally as a possible di-genic explanation for neonatal hypoglycaemia. Interpretation: Collectively these studies suggest the existence of a genetically heterogenous group of disorders that are metabolic phenocopies of AKT2-driven fasting hypoglycaemia. Further investigation of this group of naturally occurring human experiments of nature promises to yield novel information about the in-vivo regulation of fasting glucose metabolism and its perturbation in common disease. Funding: Rosetrees Trust, Wellcome Trust.